2019 IEEE Milan PowerTech 2019
DOI: 10.1109/ptc.2019.8810620
|View full text |Cite
|
Sign up to set email alerts
|

Performance Investigation of a Monitoring Scheme for Low Voltage Grids with a Single Grounded Neutral

Abstract: Low voltage distribution grids (LVDGs) are evolving from their traditional passive behavior into highly active systems. Their secure and reliable operation will require effective control schemes which in return require reliable and accurate monitoring systems. Most of the related existing works rely on the threephase Weighted Least Squares (WLS) state estimation method which is used mainly on Medium Voltage Distribution Grids (MVDGs). However due to different characteristics between MVDGs and LVDGs this method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…It can be observed that the proposed monitoring scheme with the W1 weights is considerably more accurate compared to the . As it was shown in [14], the performance of is highly affected by the zero-sequence current that is flowing in the system and therefore depends on the operating conditions. In 1 , since the neutral voltage is considered in the problem formulation, its performance not only is 6 times higher (in average) than but also significantly more stable as its affected by the operating conditions in a considerably lower degree.…”
Section: A Accuracy Class Of the Smart Metersmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be observed that the proposed monitoring scheme with the W1 weights is considerably more accurate compared to the . As it was shown in [14], the performance of is highly affected by the zero-sequence current that is flowing in the system and therefore depends on the operating conditions. In 1 , since the neutral voltage is considered in the problem formulation, its performance not only is 6 times higher (in average) than but also significantly more stable as its affected by the operating conditions in a considerably lower degree.…”
Section: A Accuracy Class Of the Smart Metersmentioning
confidence: 99%
“…In fact, in Cyprus and in many other countries the neutral conductor in a LVDG is only grounded at the MV-LV substation. If such a DSSE is used in this kind of LVDGs, then a significant error is imposed on the estimation results [14]. The main reasons for this are: (1) the inaccurate system model due to the Kron's reduction and (2) the phase-toneutral voltage measurements.…”
Section: State Estimation For Distribution Grids With a Single Point mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the transmission/distribution regulations in Cyprus, the phase-to-neutral voltage should be 230 V ± 10%. However, due to the highly asymmetric loading conditions causing a non-negligible neutral to ground voltage at each node, the phase-to-neutral voltage can exceed these limits even if the phase-to-ground voltage is well within the admissible interval [11]. This is illustrated in Fig.…”
Section: A Current Conditionmentioning
confidence: 99%
“…Due to the unbalanced nature of the LVDG and the mainly single-phase loads (asymmetric loading conditions), a significant portion of the total load current flows in the neutral conductor. Especially in a system that the neutral conductor is only grounded at the MV-LV transformer substation, this gives rise to a significant voltage drop across it [11]. By using Kron's reduction to simplify the problem and merge the neutral conductor with the phase conductors not only will yield incorrect results [12] but also important information will be lost as most loads in these kinds of systems are connected between a phase conductor and the neutral conductor.…”
Section: Introductionmentioning
confidence: 99%